Rheological and thermodynamic behaviour of PSf/ZnO: Effect of zinc oxide - Abu Mansor, Mohamad Luqman Harith; Yunos, Muhamad Zaini; Harun, Zawati; Mohamed Hatta, Mohamed Nasrul; Hussin, Rosniza; Ahmad, Azlinnorazia; Zulkefli, Aina Syazwana (International Journal of Integrated Engineering, 2019)
Zinc oxide synthesis normally involve zinc precursor and reduction during the preparation. To improve the dispersion of nanoparticle, the ZnO synthesis is the most promising option since the particles can stabilize in dope solution. However, the process of ZnO synthesis required the addition of polar precursor and reduction agents which are expected to influence the rheological and phase inversion properties of membrane dope solution. It is worth to mention that the rheological properties and phase inversion behaviour of the dope solutions play a critical role in determining the membrane morphology and separation performance. The PSf/ZnO dope solution was prepared via in-situ synthesis using three different precursors and reducing agents. The concentration was varied from 0 wt. %, 1 wt.% and 2 wt.% before dissolving in N-Methyl-2-pyrrolidone (NMP) as it will completely dissolved together. Three different precursors used were Zinc Chloride, Zinc Nitrate and Zinc Acetate while Sodium Borohydride, Hydrazine Hydrate and Urea are three different reduction agents. The thermal stability of the dope solutions was analyzed using cloud test measurement and the rheological properties were measured using viscometer toward the viscosity of the dope solution. Thermodynamic stability analysis denotes that that the hydrazine hydrate has the lowest water percentage for 15 wt.% of PSf which is 3.30 %. Meanwhile, zinc acetate with hydrazine hydrate have the lowest water percentage for 15 wt.% PSf which is 1.59 %. This also shows that the zinc chloride binodal line nearly to the solvent/polymer axis which might resulted on faster demixing rate and miscibility gap become shorter. Urea is nearest to binodal line. Viscosity test results to highest viscosity of urea as reducing agent in dope solution. Moreover, it shows that the PSf/ZnO solution have Newtonian behaviour. As the concentration of Zinc Oxide increases, the viscosity increases at the room temperature.